Utilization of Steel Aggregate and Iron Sand as Heavyweight Concrete for Gamma Radiation Shielding - Habib Abdurrahman; Iman Satyarno; Agus Budhie Wijatna (Civil Engineering Dimension, 2025)
This study aims to produce a homogenous and workable conventional heavyweight concrete (HWC) with similar performance as pre-placed HWC in attenuating radiation by increasing the concrete density with no risk of segregation. HWC was mixed using steel aggregate and iron sand with a specific gravity of 7.78 and 4.14, respectively. A w/c ratio of 0.5 was applied to obtain proper workability and viscosity modifying agent (VMA) was used to prevent segregation. The radiation tests were carried out using 133Ba (356 keV), 137Cs (662 keV), and 60Co (1170 keV & 1330 keV) gamma sources. The results obtained a concrete density of 5133.07 kg/m3 with no sign of segregation and a compressive strength of 18.61 MPa. Based on the radiation test, the conventional HWC was effective in reducing the shielding thickness by 50.41%. Our findings provide a workable conventional HWC with high gamma attenuation to replace an enormous dimension of normal concrete.